Dabigatran in the Treatment of Warfarin-Induced Skin Necrosis: A New Hope. (27th March 2016) - Bakoyiannis, Christos; Karaolanis, Georgios; Patelis, Nikolaos; Maskanakis, Anastasios; Tsaples, Georgios; Klonaris, Christos; Georgopoulos, Sotirios; Liakakos, Theodoros
Abstract : Warfarin-induced skin necrosis is an infrequent and well-recognized complication of warfarin treatment. The incidence was estimated between 0.01% and 0.1% whereas a paradoxal prothrombotic state that arises from warfarin therapy seems to be responsible for this life-threatening disease. To the best of our knowledge we present the first case of an old woman diagnosed with warfarin-induced skin necrosis, in whom novel oral anticoagulants and extensive surgical debridement were combined safely with excellent results.